Dietary Polyphenols in the Aetiology of Crohn's Disease and Ulcerative Colitis—A Multicenter European Prospective Cohort Study (EPIC). Issue 12 (December 2017) - Lu, Yunxia; Zamora-Ros, Raul; Chan, Simon; Cross, Amanda J.; Ward, Heather; Jakszyn, Paula; Luben, Robert; Opstelten, Jorrit L.; Oldenburg, Bas; Hallmans, Göran; Karling, Pontus; Grip, Olof; et al.
Abstract : Background: Oxidative stress may be involved in the aetiology of inflammatory bowel disease and whether dietary polyphenols, which possess antioxidants properties, prevent its development is unknown. Methods: A total of 401, 326 men and women aged 20 to 80 years from 8 countries were recruited between 1991 and 1998 and at baseline completed validated food frequency questionnaires. Dietary polyphenol intake was measured using Phenol-Explorer, a database with information on the content of 502 polyphenols. Incident cases of Crohn's diseases (CD) and ulcerative colitis (UC) were identified during the follow-up period of up to December 2010. A nested case–control study using conditional logistic regression estimated the odds ratios (ORs), and 95% confidence intervals, for polyphenol intake (categories based on quartiles) and developing CD or UC. Results: In total, 110 CD (73% women) and 244 UC (57% women) cases were identified and matched to 440 and 976 controls, respectively. Total polyphenol intake was not associated with CD ( P trend = 0.17) or UC ( P trend = 0.16). For flavones and CD, there were reduced odds for all quartiles, which were statistically significant for the third (OR3rd versus 1st quartile = 0.33; 95% confidence interval, 0.15–0.69) and there was an inverse trend across quartiles ( P = 0.03). Similarly, for resveratrol, there was an inverse association with CD (OR4th versus 1st quartile = 0.40; 95% confidence interval, 0.20–0.82) with an inverse trend across quartiles ( P = 0.02). No significant associations between subtypes of polyphenols and UC were found. Effect modification by smoking in CD was documented with borderline statistical significance. Conclusions: The data supports a potential role of flavones and resveratrol in the risk of developing CD; future aetiological studies should investigate these dietary components and further examine the potential for residual confounding. Abstract : Article first published online 22 August 2017.Supplemental Digital Content is Available in the Text.